#TITLE_ALTERNATIVE# - PRADIVTA (NIM : 10309024); Pembimbing : Dr. rer. nat. M. Ikbal Arifyanto, INDRI
Thick disk of the Milky Way, was first identified from a vertical density profile star with double exponential functions (Gilmore & Reid 1983), in many ways different from the thin disk. Star in a thick disc generally has a low rotational velocity, high dispersion velocity, high [α/Fe] ratio, old stars, and metal-poor than the stars in the thin disk. High [α/Fe] ratio and old stars implies that the thick disk stars formed earlier than thin disk stars. Simulation formation of a thick disk galaxy has been proposed to explain the origin of stars in the thick disc. There are two models that support the evolution and formation of a thick disc, the accretion of satellite disrupted model (Abadi et al,2003) and radial migration model (Roskar et al,2008). Accretion model estimates that more than 70% thick disk star increase from galaxy disrupted, while the radial migration model assumed that thick disk of galaxies formed by stars that migrated from inside-out of the disc as a result of corotational resonance with spiral arms. Both the simulation model were compared with observational data from the sample of Geneva-Copenhagen Surveys (GCS). Helmi et al.(2003) use simulations of accretion model and generates a thick disc with several peaks of [Fe/H] in the range 0.3 < e < 0.5. While Shonrich & Binney (2009) analyzed the impact of churning and blurring since angular momentum changes from the inside-out disc. From the results of observational seem that radial migration model is the best approach to the Milky Way.